The Influence of Shopee Express Agent Service Quality on Consumer Decisions in South Binjai - Suherni, Suherni; Fadillah, Tri Dessy (Jurnal EMT KITA, 2026)
The rapid growth of e-commerce has increased the importance of logistics services as a critical factor influencing consumer decision-making. This study aims to analyze the effect of service quality on consumer decisions in using Shopee Express (SPX) delivery services in Binjai Selatan. A quantitative approach with a causal research design was employed. Data were collected from 100 respondents who had previously used SPX services through a structured questionnaire measured using a Likert scale. The data were analyzed using validity and reliability tests, followed by multiple linear regression analysis. The results indicate that service quality has a significant influence on consumer decisions. Among the service quality dimensions, reliability has the strongest effect, followed by assurance, tangibles, and responsiveness. Meanwhile, empathy does not have a significant effect on consumer decision-making. The coefficient of determination shows that service quality explains a substantial proportion of consumer decision variance, while the remaining variance is influenced by other factors not examined in this study. These findings emphasize the importance of improving operational reliability and service assurance to enhance consumer trust and maintain competitiveness in the e-commerce logistics industry.